2011
DOI: 10.1007/s12564-011-9165-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of organizational learning in transformational leadership and organizational innovation

Abstract: Leadership is an important factor affecting organizational innovation. Many studies show that transformational leadership has positive and significant influence on organizational innovation. Based on a literature review and previous work, this study aims to investigate the influence of transformational leadership on organizational innovation and to examine whether organizational learning is a mediator between their relationships. Structural equation modeling was used to test the model. The research sample cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 60 publications
(69 reference statements)
3
70
0
3
Order By: Relevance
“…Organizational learning triggers the relationship between support for innovation and organizational innovation. In the study of Hsiao and Chang (2011) found that there is the mediate effect of organizational learning on the relationship between organizational learning and organizational innovation. This study not only found a similar result, but further support for innovation can also, through organizational learning, directly or indirectly improve organizational innovation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Organizational learning triggers the relationship between support for innovation and organizational innovation. In the study of Hsiao and Chang (2011) found that there is the mediate effect of organizational learning on the relationship between organizational learning and organizational innovation. This study not only found a similar result, but further support for innovation can also, through organizational learning, directly or indirectly improve organizational innovation.…”
Section: Discussionmentioning
confidence: 98%
“…We developed a confirmatory factor analysis (CFA) to validate our scale and showed that the four-item scale was unidimensional with high reliability (a = .92, AVE = .70). Scales that measure organizational learning based on the main participants have been widely used in recent studies (e.g., Bauer and Mulder 2013;Chang et al 2011;García-Morales et al 2006;Hsiao and Chang 2011;Rhee and Sigler 2010).…”
Section: Organizational Learningmentioning
confidence: 99%
“…Camps and Torres (2011) argued that the objective of innovation strategies was to enhance the return on investment of a business and the employees' profitability. Hsiao and Chang (2011) considered innovation strategies as the "process" transforming knowledge into useful goods, in which people, affairs, and objects as well as the interaction and information feedback among relative departments were emphasized; besides, innovation was the major source to create knowledge and expand technological knowledge. Innovation strategies therefore were the primary tactic for a nation or a business promoting the competitiveness.…”
Section: Knowledge Managementmentioning
confidence: 99%
“…Knowledge management capabilities Bolívar-Ramos et al (2012) regarded knowledge management as the process to practice organizational objectives and further indicated that knowledge management could present organizational design and was the aggregation of operation principles and process application techniques to create value for the business. Hsiao and Chang (2011) considered that the knowledge architecture was composed of technology, structure, and culture with knowledge acquisition, transformation & application, and protection; it was the meaning of knowledge management. Mirkamali et al (2011) pointed out knowledge as the asset of knowledge management capabilities, including the inventory, evaluation, monitoring, regulation, acquisition, learning, distribution, protection, and innovation of knowledge to enhance knowledge assets.…”
Section: Research Motivation and Backgroundmentioning
confidence: 99%